2020
DOI: 10.1007/s00345-020-03437-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of robot-assisted residual mass resection in metastatic nonseminomatous germ cell tumor

Abstract: Purpose To evaluate the outcome of robot-assisted residual mass resection (RA-RMR) in nonseminomatous germ cell tumor (NSGCT) patients with residual tumor following chemotherapy. Patients and methods Retrospective medical chart analysis of all patients with NSGCT undergoing RA-RMR at two tertiary referral centers between January 2007 and April 2019. Patients were considered for RA-RMR in case of a residual tumor between 10 and 50 mm at cross-sectional computed tomography (CT) imaging located ventrally or lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Thus, especially at the implementation of the technique, one has to bear a higher complication rate in mind, and starting in patients with limited disease seems reasonable. In summary our results are in line with the results of other large volume series on R-RPLND 22 , 27 , 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, especially at the implementation of the technique, one has to bear a higher complication rate in mind, and starting in patients with limited disease seems reasonable. In summary our results are in line with the results of other large volume series on R-RPLND 22 , 27 , 28 .…”
Section: Discussionsupporting
confidence: 92%
“…To date, most of the studies on R-RPLND have reported on pR-RPLND 10 , 18 , 22 25 , with the largest cohort comprising 58 patients including mainly CS 1 tumours 22 . Only a few publications on pcR-RPLND are available 11 , 12 , 26 , 27 , with the largest series comprising 45 patients 27 . So far, only one other publication exists on R-RPLND in a mere mTGCT patient collective, comprising both pR-RPLND (n = 22) and pcR-RPLND (n = 4) patients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 37 studies [7,21–56] were included. Of these, 12 studies [7,21,23–25,28–32,34,35] described patients who underwent primary R‐RPLND only, 16 [38–53] described patients who underwent post‐chemotherapy R‐RPLND only, and six [22,26,27,33,36,37] included patients who underwent R‐RPLND in either of these settings.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 37 studies [7,21–56] were included. Of these, 12 studies [7,21,23–25,28–32,34,35] described patients who underwent primary R‐RPLND only, 16 [38–53] described patients who underwent post‐chemotherapy R‐RPLND only, and six [22,26,27,33,36,37] included patients who underwent R‐RPLND in either of these settings. Two studies involving post‐chemotherapy RPLND were published from the same centre at two different time periods [39,41]; hence, the series published on a later date was included in the cumulative analysis [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation